The evaluation of high-and moderate-intensity interval exercise on perceptual responses, physical health, quality of life, mental well-being and exercise motivation among college students in China - Ming, Chang (2025)
The prevalence of physical inactivity among college students has become a serious challenge for the education and health authorities across many regions in the world, including China. Consequently, researchers and health providers have shifted their attention to interval-type of exercise as a potentially effective strategy to promote physical activity. However, it is unclear whether different intensities of interval exercise could promote exercise adherence and overall wellness among college students. The present study examined the effects of different work intensities during interval exercise training on the perceptual responses, physical health parameters, exercise motivation, mental well-being and health-related quality of life (HRQOL) in physically inactive college students. Twenty-four inactive college students (aged 20.8 ± 1.2 years; PA levels = 448 ± 80 MET-min/week) were randomly assigned to two groups: High-Intensity Interval Exercise (HIIE) or Moderate-Intensity Interval Exercise (MIIE). Both groups underwent 12 weeks of exercise intervention, with 6–10 × 1-minute work intervals at 90% of Maximal Aerobic Speed (MAS) for HIIE and 6–10 × 1-minute work intervals at 60% of MAS for MIIE. The exercise sessions were conducted three times per week, for a total of 36 sessions. Perceptual responses (affective, enjoyment, and perceived exertion) observed in sessions 1, 18, and 36 were measured. Whereas physical health parameters (cardiorespiratory fitness and body composition), exercise motivation, mental well-being (stress, depression, and anxiety) and HRQOL were measured before and after 12-week exercise intervention. The results of the Mixed Factorial Analysis of Variance displayed significant interactions between experimental groups across the measurement sessions compared to the control group for feeling scale (FS), enjoyment, cardiorespiratory responses, anxiety, depression, HRQOL, and exercise motivation. The results of post–hoc analysis displayed that HIIE group generated lower affective responses at work interval 4 and end work interval in session 1 and session 18 compared to MIIE group (all P < 0.05). However, HIIE elicited greater score in FS at the end of the work interval during sessions 18 and 36 compared to session 1 (P < 0.05). Both groups generated greater post-enjoyment in session 36 compared to session 1 (all P < 0.05). A significant improvement in cardiorespiratory responses and body composition was observed in HIIE group compared to MIIE group following a 12-week intervention (P < 0.05). Also, HIIE group produced a significant improvement in anxiety and depression scores following a 12-week intervention compared to MIIE group (all P < 0.05). HIIE elicited an improvement from baseline in overall HRQOL variables (all P < 0.05) compared to only two HRQOL variables in MIIE group (all P < 0.05). A significant improvement in intrinsic and identified scores were also observed (all P < 0.05) after HIIE intervention. In contrast, MIIE group elicited greater scores in external and amotivation following exercise intervention (all P < 0.05). HIIE appears to be a time-efficient and viable strategy to facilitate future exercise adherence while producing overall physical and mental well-being among physically inactive college students when considering the impact of perceptual responses, overall physical health parameters, and exercise motivation factors.